Numerical Simulations of Subcooled Nucleate Boiling for a Power Electronic Device - Pettersson, Jonas (My University, 2015)
The growing demand for power in today’s society require large power grids containing high power electronic devices, of which ABB is a leading manufacturer. In these devices power losses inevitably occur, leading to heat generation. The heat eventually causes the device to fail, hence cooling such devices are of great importance. A way to cool such a system is by liquid cooling with phase change (subcooled nucleate boiling) as an energy transport phenomenon. To develop such cooling systems, a mathematical model with a numerical solution procedure is needed to predict the physical properties. To achieve this, a literature study has been carried out to formulate a closed mathematical system, describing this problem. The formulated model is based on previously verified models for boiling properties, such as bubble diameters, wall super heat, heat flux, mass transfer due to evaporation and condensation. These models were combined with a new approach to calculate wall temperature. The new wall temperature was introduced to save computational time, since this often is an issue when implementing these types of models. A case with existing experimental data, found in the literature study, was simulated and the results were compared with varying agreement. The vapour content proved to be under predicted by the model and the introduced wall temperature model gave over predicted results. Good agreement could be seen of the evaporation heat fluxes with some dependency of the bubble diameter in the system. Despite over and under predictions, the trends of several properties agreed with the reference data. The developed solver also performed stable computations and was well documented, preparing it for future development. KEYWORDS: CFD, OpenFOAM, subcooled nucleate boiling flow, wall temperature, bubble diameter model, heat flux partitioning, cooling
Keywords: Grundläggande vetenskaper; Matematik; Basic Sciences; Mathematics